Social Context of Service Use Among Homeless Youth in Los Angeles, California. Issue 42 (7th August 2016) - Barman-Adhikari, Anamika; Petering, Robin; Lengnick-Hall, Rebecca; Rice, Eric; Rhoades, Harmony; McCune, Sarah
ABSTRACT: Little is known about rates and correlates of service use or the role that social context plays in service engagement among homeless youth. This study compares two distinct service areas and uses a social network approach to examine how environmental factors (e.g., neighborhood), social factors (e.g., social capital and network engagement) and individual level factors that relate to service use patterns among homeless youth in Los Angeles, California. A sample of 938 youth was recruited from three drop-in centers in two distinct service sites. Individuals were surveyed about their individual and social network attributes. Univariable and multivariable analyses were utilized to understand the influence of social-contextual variables on service use. Service use behaviors varied across site and service type with youth in Hollywood showing greater engagement than youth at the Beach site. Across both sites and several service types, staff emotional support was positively correlated with levels of service use. The site comparisons also point to the fact that even within a single geographic area, like Los Angeles County, client profiles and rates of service use can significantly vary. Future research needs are presented with specific emphasis on understanding the needs of non-service-seeking youth.